Organization and ВIM modeling of the construction of objects based on the concept of value construction management - Kalashnikov, D.; Bohatiuk, D.; Filippov , О. (Ways to Improve Construction Efficiency, 2022)
The article explores the possibility of using conceptual approaches, methods and techniques and the very ideology of value-oriented management for the administration of investment and construction projects.Building Information Modeling (BIM) models are very useful when implementing cost-based construction management because they provide a data-rich environment that allows construction managers to make data-driven decisions about costs, materials and resources. This helps to optimize cost control and overall project management.The following advantages of value-oriented management in the implementation of construction projects have been identified, namely: increased cost efficiency, project cost management, risk reduction and the possibility of managing them, social and environmental effects, increased satisfaction of project participants and investors, obtaining additional competitive advantages of construction products, development innovations and introduction of new technologies, expansion of cooperation with stakeholders.Building Information Modeling (BIM) models can be useful when implementing cost-based construction management because they contain detailed information about the components and materials used in a construction project, provide a visual representation of the project, allow stakeholders to visualize the design and construction process, allow perform cost analysis at different stages of the project, allow for the identification of overlaps, conflicts or conflicts in the design, facilitate cost calculations when design decisions change, allowing project teams to explore alternative design and construction options, can be used to estimate the long-term costs of the life cycle of a building, including maintenance and operation costs.